The implementation of informative advertisement in blood donation awareness campaign to public / Muhamad Fadzrul Rahmat - Rahmat, Muhamad Fadzrul (2013)
Blood donation is carried out when a person voluntarily agrees for blood to be drawn with the intention of donating it. The donated blood may be used for transfusions or it may be separated into individual components to be used as required. The latter procedure is called fractionation. Blood donation may be of different kinds. In the developed countries unpaid donors give blood to replenish a community supply. In economically poorer countries, however, blood donation is carried out according to demand, as the established blood ties are extremely limited. It may be an altruistic act or it may include a cash payment or incentives other than money. A person can have blood drawn and stored for own future use.